Improving Grade 3 Students' Beginning Reading Skills Through the Peel and String Syllable Method - Nurafni, Nurafni; Wilade, Surahman; Aqil, Muhammad; Rizal, Rizal (Papanda Publisher, 2025)
Early reading proficiency is fundamental for academic success, yet many elementary students struggle with foundational literacy skills. This study investigated the effectiveness of the syllabic peel and arrange method in improving early reading skills among third-grade students. A classroom action research design following the Kemmis and McTaggart model was implemented across two cycles with 12 third-grade students at State Elementary School 03 Malala, Indonesia. Data were collected through oral reading tests using a four-aspect rubric and structured observation sheets. The intervention employed systematic syllable recognition, word formation, and sentence construction activities supported by manipulative materials and peer-assisted learning. The intervention yielded substantial improvements across assessment phases. Classical absorption increased from 56.0% (pre-action) to 69.9% (Cycle I) and 79.8% (Cycle II), while classical completeness rose from 25% to 41% and 58% respectively. Students achieving mastery (≥65) increased from 3 (25%) to 7 (58%), with four students attaining perfect scores by Cycle II. Teacher and student activity observations demonstrated progressive improvement, reaching